MEMBANGUN KEDISIPLINAN BELAJAR MELALUI STRATEGI PENGELOLAAN KELAS: ANALISIS PADA PESERTA DIDIK - Sarifah Aini Nasution; Ani Fidria; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to analyze classroom management strategies implemented by teachers in an effort to improve students' learning discipline. Discipline is one of the important factors that influence the success of the learning process. However, in practice, various obstacles are still found, such as low student compliance with class rules and lack of responsibility in completing assignments. This study uses a qualitative approach with a literature study method, which examines various literature related to classroom management theory and learning discipline. The results of the study indicate that effective classroom management strategies include the application of clear rules, consistency in enforcing discipline, the use of a positive approach, and strengthening interpersonal relationships between teachers and students. By implementing these strategies, teachers can create an orderly and conducive learning environment that encourages increased student discipline. These findings are expected to be a reference for education practitioners in improving the effectiveness of learning in the classroom.